The Relationship Between Dual Role Conflict, Self-Adjustment, and Stress Coping in Wives Who Work as Factory Workers - Nadia Putri; Prinska Damara Sastri (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to examine the relationship between dual role conflict and self-adjustment with stress coping mechanisms in wives who work as factory workers. The study used a quantitative correlational design. Data collection was conducted on 60 factory worker wives selected through purposive sampling, with the criteria of being aged 25–40 years, having at least one child, having been married for at least 2 years, and residing in Cangkuang Wetan Village, Dayeuhkolot District, Bandung Regency. Variable measurements were conducted using three psychological scales that had been tested for validity, namely the dual role conflict scale, the self-adjustment scale, and the stress coping scale. Descriptive analysis results showed that most respondents (60%) were in the high dual role conflict category, while 50% were at a moderate level of self-adjustment. In addition, 51.6% of respondents showed high levels of stress coping. Regression analysis showed that self-adjustment had a positive and significant effect on stress coping, while dual role conflict did not show a significant partial effect. However, simultaneous testing showed that dual role conflict and self-adjustment together had a significant effect on stress coping, with an F value of 30.334. These findings indicate that greater dual-role conflict requires greater use of stress-coping strategies, while effective self-regulation skills contribute to greater stress-coping effectiveness